An economic model of the meat paradox - Nina Hestermann; Yves Le Yaouanq; Nicolas Treich (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2019)
Many individuals have empathetic feelings towards animals but frequently consume meat. We investigate this "meat paradox" using insights from the literature on motivated reasoning in moral dilemmata. We develop a model where individuals form self-serving beliefs about the suffering of animals caused by meat consumption in order to alleviate the guilt associated with their dietary choices. The model makes several specific predictions: in particular, it predicts a positive relationship between individuals' taste for meat and their propensity to engage in self-deception, a high price elasticity of demand for meat, and a causal effect of prices and aggregate consumption on individual beliefs.
Keywords: D72; D81; D83; D84; Z13; 330; motivated reasoning; moral dilemmata; self-deception; meat paradox; meat price-elasticity; animal welfare